THE INFLUENCE OF SWIMMING IN DEVELOPMENT OF MOTOR COORDINATION OF CHILDREN WITH DOWN SYNDROME (Fiep Bulletin - online, 2013)
Swimming is one of mankind oldest physical activities, where the man wishing to maintain its ideals of beauty swim with the goal of achieving the perfection or even have a physically strong body, since it was used to prepare soldiers for future battles fit. Currently swimming is a very popular physical activity, being more present in the media thanks to its great results in the Paralympic and Olympic Games, swimming is also known for numerous physical, social and mental benefits that provides to people. For people with disabilities it helps develop motor coordination, aerobic condition and reduces spasticity, resulting in less fatigue than other physical activities. So, it is becoming one of the most appropriated activities for children with Down Syndrome. Thus, this study aims to critically dialogue about the influence of swimming in the development of motor skills of children with Down syndrome. To this end, we will maintain our notes in the literature. We hope that our notes help to expand studies on this topic, since research regarding the influence of swimming for the coordination of children with Down syndrome is not yet actual on the agenda of scientific studies developed in the area of education / activity physics.
Keywords: Motor Coordination; Down Syndrome; Swimming